Analysis of Inclusive Teaching Strategies for Addressing Communication Disorders in Children with Down Syndrome: A Case Study at SLB - Rusdiansyah, Rusdiansyah; Sudana, Dadang (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study explores the inclusive teaching strategies employed at SLB Bandung and their impact on the communication abilities of children with Down syndrome. Utilizing a descriptive qualitative design, the research provides a detailed examination of the methods, challenges, and outcomes within the context of a special education school in Bandung, Indonesia. Data were collected through in-depth interviews with teachers, classroom observations, and document analysis to ensure a comprehensive understanding. The findings reveal that individualized instruction, visual aids, and frequent communication practice are pivotal strategies used by teachers to enhance the communication skills of children with Down syndrome. These methods align with best practices in special education and are positively received by both educators and parents. However, significant challenges remain, including limited resources, the need for specialized training, and notably, the absence of speech therapy services at the school. Classroom observations and document analysis highlight the dynamic and interactive nature of these inclusive strategies. The commitment and creativity of teachers in implementing these strategies, despite the challenges, are evident. The study concludes that while inclusive teaching strategies significantly contribute to the communication development of children with Down syndrome, addressing resource limitations and incorporating speech therapy services are essential for maximizing student outcomes. Recommendations include enhancing collaboration among educators, policymakers, and therapists to improve the quality of inclusive education and ensure equitable support for all students.